2015
DOI: 10.1515/polyeng-2015-0030
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of indentation size effects and depth dependent mechanical properties of elastic polymers

Abstract: Abstract Indentation size effects have been observed in both polymers and metals but, unlike in metals, the origin of size effects in polymers is not well understood. To clarify the role of second order gradients of displacements, a model polymer is examined with spherical and Berkovich tips at probing depths between 5 and 25 μm. Applying different theories to determine the elastic modulus, it is found that with a pyramidal tip, the elastic modulus increases with decreasing ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 44 publications
4
28
0
Order By: Relevance
“…Therefore, strain/rotation gradient based models [22e23] would not predict h dependence in the hardness. It has been also experimentally observed that applying such a spherical tip, rotation gradients essentially do not change with h [37]. In Fig.…”
Section: Influence Of Rotation Gradients On the Depth Dependent Deformentioning
confidence: 61%
“…Therefore, strain/rotation gradient based models [22e23] would not predict h dependence in the hardness. It has been also experimentally observed that applying such a spherical tip, rotation gradients essentially do not change with h [37]. In Fig.…”
Section: Influence Of Rotation Gradients On the Depth Dependent Deformentioning
confidence: 61%
“…Indentation testing has been widely applied to characterize and determine properties of materials at nano-to micrometer length scales [1][2][3][4][5][6][7][8][9][10][11][12]. The deformation mechanisms and behavior at these length scales can be significantly different compared to those at the macroscopic length scale, and nanoindentation testing has been a vital tool to unravel these differences.…”
Section: Introductionmentioning
confidence: 99%
“…, a large indentation recovery occurs in LNKCP glass during unloading above T g compared with LP glass. Such recovery is unusual indentation behavior in oxide glasses, although it is known from organic glasses …”
Section: Discussionmentioning
confidence: 94%
“…Such recovery is unusual indentation behavior in oxide glasses, although it is known from organic glasses. [20][21][22] The P-h curves of LNKCP glass at 493-523 K and LP glass at 613 K were analyzed with the viscous-elastic-plastic (VEP) model, 19 which describes the sharp indentation behavior of time-dependent materials. Figure 4 shows a schematic illustration of the model.…”
Section: Discussionmentioning
confidence: 99%